Analysis of Professional Skepticism and APIP Competence on Audit Quality (A Study at the Inspectorate of Southwest Aceh Regency) - Melawati, Melawati; Marlina, Lilis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to analyze the influence of professional skepticism and the competence of APIP (Internal Government Auditors) on audit quality at the Inspectorate of Southwest Aceh Regency, using a Likert scale. The research is motivated by studies highlighting the impact of audits on government losses caused by the development of the Integrated Information System of the Abdya Creative Industry Center (PIKA). The population of this study consists of all staff at the Inspectorate Office of Southwest Aceh Regency, totaling 49 individuals, with a purposive sampling technique and a sample size of 31 auditors involved in field audits and evidence documentation. The results of the study show that professional skepticism does not have a significant impact on audit quality, while APIP competence has a positive and significant impact on audit quality. These findings provide important insights for the Inspectorate of Southwest Aceh Regency to focus more on improving auditor competence to enhance audit quality outcomes.